Bimetal Organic Framework Derived Atomically Dispersed Mn and N Codoped Porous Carbon for Efficient Oxygen Reduction. Issue 43 (21st September 2021) - Yang, Yanan; Sun, Chaoyong; Zhang, Huabing; Ke, Shaojie; Liu, Haitao; Dou, Meiling; Wang, Feng
Abstract: Developing cost‐effective non‐precious metal electrocatalysts (NPMCs) for the sluggish oxygen reduction reaction (ORR) is critical for the large‐scale application of metal‐air battery and fuel cell technologies. Herein, we present an effective Mn/Zn bimetal organic frameworks (MOFs)‐based strategy to synthesize an efficient manganese (Mn) and nitrogen (N) co‐doped porous carbon electrocatalyst with atomically dispersed N‐coordinated single Mn moieties (Mn‐Nx ) for ORR catalysis. This strategy involves the adsorption of Mn ions into the Mn/Zn bimetal MOFs followed by the subsequent pyrolysis in Ar and then activation in NH3 . Owing to the atomically dispersed Mn‐Nx sites, the large specific surface area and the high content of graphitic‐N, the resulting electrocatalyst shows a superior ORR activity with a half‐wave potential of 0.885 V and an outstanding electrochemical durability in alkaline electrolyte outperforming commercial Pt/C, and it also exhibits a superior performance for an assembled primary Zn–air battery. This work offers a new prospect for the synthesis of MOFs‐derived highly efficient NPMCs for ORR. Abstract : Atomically dispersed Mn and N co‐doped porous carbon electrocatalyst was prepared through an effective Mn/Zn bimetal MOFs‐based strategy. The resulting electrocatalyst shows a superior ORR activity with a half‐wave potential of 0.885 V and an outstanding electrochemical durability in alkaline electrolyte outperforming commercial Pt/C, and it also exhibits a superior performance for the assembled primary Zn–air battery.